2023
DOI: 10.3390/ijms24076302
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Impact of Sex Hormones on the Immune System

Abstract: Sex hormones are key determinants of gender-related differences and regulate growth and development during puberty. They also exert a broad range modulation of immune cell functions, and a dichotomy exists in the immune response between the sexes. Both clinical and animal models have demonstrated that androgens, estrogens, and progestogens mediate many of the gender-specific differences in immune responses, from the susceptibility to infectious diseases to the prevalence of autoimmune disorders. Androgens and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 91 publications
2
10
0
1
Order By: Relevance
“…According to our findings, females had higher median concentrations of SARS-CoV-2 antibodies than males. This supports the theory that after disease exposure, females have higher antibody production compared to males because male androgens suppress the immune response (40). Contrary to our findings, several other studies have found that male HCWs have higher SARS-CoV-2 antibodies than female HCWs, inferring to behavioural differences (25,27,37,41,42).…”
Section: Discussionsupporting
confidence: 79%
“…According to our findings, females had higher median concentrations of SARS-CoV-2 antibodies than males. This supports the theory that after disease exposure, females have higher antibody production compared to males because male androgens suppress the immune response (40). Contrary to our findings, several other studies have found that male HCWs have higher SARS-CoV-2 antibodies than female HCWs, inferring to behavioural differences (25,27,37,41,42).…”
Section: Discussionsupporting
confidence: 79%
“…Sex hormones can affect the immune system, and there is a strong link between the gut microbiome and the immune system 21 . Changes in sex hormones may affect the immune system's response, 53 which in turn affects the balance of the gut microbiome. For example, sex hormones can affect the activity of immune cells, which can have an effect on the intestinal immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormones can affect the immune system, and there is a strong link between the gut microbiome and the immune system. 21 Changes in sex hormones may affect the immune system's response, 53 which in turn affects the balance of the gut microbiome.…”
Section: F I G U R Ementioning
confidence: 99%
“…Previous studies also link SARS-CoV-2 infection and members of the Herpesviridae Family to AD development through modulation of AD-related processes via virus-host protein-protein interactions ( 67 , 68 ). Women generally exhibit stronger immune responses, making them more effective at fighting infections ( 69 ), but potentially increasing susceptibility to immune-mediated diseases ( 70 ). Sex hormones, particularly estrogen in women, modulate immune cell function ( 71 , 72 ).…”
Section: Discussionmentioning
confidence: 99%